DOI: 10.17077/etd.l1o4bniu
|View full text |Cite
|
Sign up to set email alerts
|

Flow structure in the wake of a low-aspect-ratio wall-mounted bluff body

Abstract: Mean dimensionless reattachment lengths on the symmetry plane measured from the obstacle center line, and nondimensionalized by obstacle height (which remains constant for all obstacles) and obstacle diameter. 4.2 Circulation of base vortex in different relative submergence in Figure 4.14. 4.3 Average dimensionless circulations of structures identified for streamwise and transverse ellipsoid at x/H = 1.5 in two different turbulence intensity, and the left/right deviation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 93 publications
(309 reference statements)
0
2
0
Order By: Relevance
“…The wake structures, vortex shedding behavior, and primary parameters governing the flow fields around wall-mounted obstacles including obstacle shape, aspect ratio (AR = height/width = H/D), boundary layer characteristics, and Reynolds number have been studied extensively for decades as reviewed in detail by Hajimirzaie (2013). In particular, much attention has been given…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wake structures, vortex shedding behavior, and primary parameters governing the flow fields around wall-mounted obstacles including obstacle shape, aspect ratio (AR = height/width = H/D), boundary layer characteristics, and Reynolds number have been studied extensively for decades as reviewed in detail by Hajimirzaie (2013). In particular, much attention has been given…”
Section: Introductionmentioning
confidence: 99%
“…In the case of dipole wakes, bending and reconnection of Kármán vortices occurs only at the free end resulting in a "half-loop" structure (Hosseini et al, 2013). Hajimirzaie (2013) reviewed the wake structures and shedding dynamics of wall-mounted bodies of AR ≈ 1 including hemispheres, spheres, tapered plates, pyramids, and cones. In particular, the detailed review of research on the origins of vortices in the near wake demonstrated that the wake structures (tip, base, and spanwise vortices) and their dynamics can be highly varied for obstacles of AR ≈ 1 depending on obstacle shape and flow conditions (i.e., Re and δ/D or δ/H).…”
Section: Introductionmentioning
confidence: 99%